CHALLENGES OF LEGAL TERMS TRANSLATION: NATIVE RUSSIAN TRANSLATORS’ PERCEPTIONS IN THE FOCUS - Belenkova, Nataliya; Kruse, Irina (International Journal of Psychosocial Rehabilitation, 2020)
The current research has the following goal: to compare and analyze the translations of various legal terms and concepts that have been already generally accepted in the theory and practice of legal translation. During the research, a great scope of theoretical and practical materials is examined. The experimental comparative analysis was held mainly on the basis of the open-access documents of the European Union and the Federal and Regional laws of the Russian Federation. The methods of the research included the study of the contemporary research on the issue, the comparative analysis of the legal terminology used in English and Russian legal setting, a translators’ survey and a statistical method of processing research results. The output of the research identified modern challenges of legal translation within Russian-English working language pairs. The research findings can be used in the practical activity of the translators working in the legal domain as well as in training translators-to-be in Higher Education Institutions